2011
DOI: 10.1103/physrevlett.107.197203
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of Spin Waves by Thermal Spin-Transfer Torque

Abstract: We observe amplification of spin-wave packets propagating along a film of single-crystal yttrium iron garnet subject to a transverse temperature gradient. The spin waves are excited and detected with standard techniques used in magnetostatic microwave delay lines in the 1-2 GHz frequency range. The amplification is attributed to the action of a thermal spin-transfer torque acting on the magnetization that opposes the relaxation and which is created by spin currents generated through the spin-Seebeck effect. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 34 publications
(47 reference statements)
1
60
0
Order By: Relevance
“…Padrón-Hernández et al [93] found that magnon wavepackets propagating along a YIG film are amplified when a temperature gradient is applied perpendicular to the YIG film. This experiment implies that the magnon damping term is canceled by the action of the temperature gradient, which leads to an amplification of the magnon wavepacket.…”
Section: Effects Of Heat Current On Magnon Dynamicsmentioning
confidence: 99%
“…Padrón-Hernández et al [93] found that magnon wavepackets propagating along a YIG film are amplified when a temperature gradient is applied perpendicular to the YIG film. This experiment implies that the magnon damping term is canceled by the action of the temperature gradient, which leads to an amplification of the magnon wavepacket.…”
Section: Effects Of Heat Current On Magnon Dynamicsmentioning
confidence: 99%
“…The thickness of the YIG is only 200 nm, which is very low compared to other studies. 6,11,12,20,21 The YIG layer has a roughness of 0.4 nm. X-ray diffraction was used in order to estimate the quality of the thin layer of YIG.…”
Section: A Sample Descriptionmentioning
confidence: 99%
“…In addition, this heating probably leads to substantial changes in the magnetic properties, for instance in the exchange bias field of the reference layers. Finally, the temperature gradients are unusually strong, and may lead to additional sources of spin torques [25] that can play a role in the magnetization dynamics. Our findings imply that taking into account the current-induced heating at the nanoscale is essential for the understanding of magnetization dynamics in nanocontact systems.…”
mentioning
confidence: 99%